2014
DOI: 10.1039/c3fo60391a
|View full text |Cite
|
Sign up to set email alerts
|

Peptides accompanying chicken egg yolk IgY – alternative methods of isolation and immunoregulatory activity

Abstract: In the hen immune system the egg content plays as significant a role in the development of the chick as colostrum does in newborn mammals. One of the most important proteins in this system seems to be the main yolk immunoglobulin IgY. It has been shown that IgY is accompanied by an immunostimulatory polypeptide complex named yolkin. In this report the biological activities of yolkin separated by means of four different procedures are presented. It was shown that yolkin acts as an inducer rather than a modulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…It was shown by Polanowski et al [6,7] that hen egg yolk immunoglobulin Y occurs as a complex with polypeptides, named yolkin, which are homologous with the C-terminal domain of vitellogenin II. In our previous studies, we reported that yolkin is a good immunoregulator and stimulates human whole blood cells to produce significant amounts of cytokines [6][7][8]. In the present study, we explained the mechanism of action of the yolkin polypeptide complex in murine bone marrow-derived macrophages (BMDM cell line).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…It was shown by Polanowski et al [6,7] that hen egg yolk immunoglobulin Y occurs as a complex with polypeptides, named yolkin, which are homologous with the C-terminal domain of vitellogenin II. In our previous studies, we reported that yolkin is a good immunoregulator and stimulates human whole blood cells to produce significant amounts of cytokines [6][7][8]. In the present study, we explained the mechanism of action of the yolkin polypeptide complex in murine bone marrow-derived macrophages (BMDM cell line).…”
Section: Discussionmentioning
confidence: 75%
“…Whereas fractions of MW higher than 16 kDa are glycoproteins corresponding also to the amino acid sequence of vitellogenin II starting at position 1572aa [6]. Our studies obtained up to now have demonstrated that yolkin possesses immunoregulatory, antioxidant, and neuroprotective activities, stimulating human whole blood (ex-vivo) to produce a wide spectrum of cytokines [6][7][8], downregulating the level of intracellular free oxygen radicals, and stimulating neuron-like cells to produce brain-derived neurotrophic factor (BDNF) [9].…”
Section: Introductionmentioning
confidence: 73%
“…The mechanism of action of Yolkin is still under investigation. The recently obtained results indicate that Yolkin stimulates human whole blood cells to release cytokines: IL-6 and IL-10, shows the ability to modulate the nitric oxide (NO) production by mouse macrophages and protects against lipid peroxidation (Zabłocka et al 2014 ). Also, Yolkin stimulates neuronal cells to produce and release the mature form of BDNF (the latest unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…The natural source of yolkin is the yolk of a laying hen's egg. The methods applied for its isolation [8,10,18] allow one to obtain a heterogeneous group of yolk-derived peptides, alongside IgY purification; nevertheless, the purification yield of both methods is not high [8]. Nowadays, another approach to produce different biopeptides involves recombinant DNA technology.…”
Section: Introductionmentioning
confidence: 99%